2008
DOI: 10.1111/j.1570-7458.2008.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Stylet penetration behavior of Myzus persicae related to transmission of Zucchini yellow mosaic virus

Abstract: The direct current electrical penetration graph (DC‐EPG) technique was used to identify stylet penetration behaviors of Myzus persicae (Sulzer) (Hemiptera: Sternorrhyncha: Aphididae) that are related to successful acquisition and inoculation of the non‐persistently transmitted potyvirus, Zucchini yellow mosaic virus (ZYMV), to melon, Cucurbita pepo L. (Cucurbitaceae). Stylet penetration behaviors of two sources of M. persicae that differ in their ZYMV transmission efficiency were examined to determine if behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…One biotype of soybean aphid ( Glycine max ) was also shown to have a higher number of potential drops when feeding on resistant genotypes than on susceptible genotypes [ 11 ]. It has been reported that potential drops are related with aphid transmission of non-persistently transmitted viruses [ 68 , 69 ]. However, it is unknown if they are indicative for a specific plant resistance component.…”
Section: Discussionmentioning
confidence: 99%
“…One biotype of soybean aphid ( Glycine max ) was also shown to have a higher number of potential drops when feeding on resistant genotypes than on susceptible genotypes [ 11 ]. It has been reported that potential drops are related with aphid transmission of non-persistently transmitted viruses [ 68 , 69 ]. However, it is unknown if they are indicative for a specific plant resistance component.…”
Section: Discussionmentioning
confidence: 99%
“…This technique electrically records the changes in resistance that relate to the different stylet penetration activities of sucking insects, providing information on stylet tip position in specific plant tissues and time spent at each location (Tjallingii, 1985). The EPG technique has been applied to understand pathogen transmission by insect vectors (Powell, 1991;Fereres & Collar, 2001;Symmes et al, 2008;Sandanayaka et al, 2013a) by correlating stylet penetration activities to acquisition and inoculation of pathogens by insect vectors (Martin et al, 1997;Tjallingii & Prado, 2001;Stafford et al, 2009;Moreno et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The EPG technique has been widely used to study nonpersistent virus transmission by aphids (e.g., Mart ın et al, 1997;Symmes et al, 2008) as well as resistance, e.g., of Hordeum bulbosum (L.) to Rhopalosiphum padi (L.) (Schliephake et al, 2013), potatoes to M. persicae (Alvarez et al, 2006), and various Brassica forms to Brevicoryne brassicae (L.) (Cole, 1994).…”
Section: Introductionmentioning
confidence: 99%